2009
DOI: 10.1007/s00056-009-8808-6
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-Polymorphismen im Zusammenhang mit externen apikalen Wurzelresorptionen (EAWR)

Abstract: The available data of the IL-1A polymorphism point to an association of the genotype 2-2 with EARR. As analyses of individual subgroups showed, with the increase in the extent of EARR there was a recognizable correlation with genotype 2-2. The genotype distribution of the IL-1B polymorphism in patients and control cohorts revealed no indication of a predisposition. Despite the low number of cases in the own cohort, the data collected revealed that the allele 1 of the IL-1B polymorphism in patients with sporadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
4
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 37 publications
4
47
4
3
Order By: Relevance
“…The results of the present review suggest that although some authors have reported that genetic polymorphism may play a role in EARR, [4][5][6][7][8][9][20][21][22][23]24 others have not supported this association. [25][26] Published orthodontic investigations in gene studies have seldom adhered to the STREGA or any genetic guidelines.…”
Section: Summary Of Evidencecontrasting
confidence: 63%
“…The results of the present review suggest that although some authors have reported that genetic polymorphism may play a role in EARR, [4][5][6][7][8][9][20][21][22][23]24 others have not supported this association. [25][26] Published orthodontic investigations in gene studies have seldom adhered to the STREGA or any genetic guidelines.…”
Section: Summary Of Evidencecontrasting
confidence: 63%
“…menhang mit der Entstehung von schwergradigen Wurzelresorptionen bei kieferorthopädischer Behandlung stehen sollen: IL-1A (Interleukin-1α), IL-1B (Interleukin-1β), TNFα (Tumornekrosefaktor-α), TNFRSF11A (receptor activator of nuclear factor-kappa B (RANK)) und TNSALP (non-specific alkaline phosphatase) [2,3,4,17,20,61]. Bisher gelang es Gülden et al [17] für IL-1A sowie Al-Qawasmi et al [2] und Bastos et al [6] für IL-1B Polymorphismen zu identifizieren, die gehäuft im jeweils untersuchten Patientengut mit externen apikalen WR vorkamen. Nach Al-Qawasmi et al [2] ist eine Mutation von IL-1B für 15% der Variabilität der WR an OK-Inzisivi verantwortlich und Personen, die homozygot für dieses Allel sind, haben ein 5,6fach erhöhtes Risiko einer WR von mehr als 2 mm im Vergleich zu den Heterozygoten.…”
Section: Methodsunclassified
“…Harris et al [19] estimated that the proportion of the hereditary component is 60% -80% for external apical RR in patients undergoing orthodontic treatment. Animal and human studies have proposed various candidate genes potentially directly linked to the development of severe root resorption: IL-1A (interleukin-1α), IL-1B (interleukin-1β), TNF-α (tumor necrosis factor-α), TNFRSF11A [receptor activator of nuclear factor-kappa B (RANK)] and TNSALP (non-specific alkaline phosphatase) [2,3,4,17,20,61]. Polymorphisms linked to external apical RR in specific patient groups were identified by Gülden et al [17] for IL-1A and by Al-Qawasmi et al [2] and Bastos et al [6] for IL-1B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, a number of case-control studies (Al-Qawasmi et al, 2003a;Bastos Lages et al, 2009;Gülden et al, 2009;Tomoyasu, 2009;Iglesias-Linares, 2012a,b;Linhartova, 2012) have been conducted to investigate the association between the IL-1β +3954 C>T polymorphism and EARR risk in orthodontic treatment patients. However, the results of these studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%